Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have problems with two exercises. I know the answer of those two but both of them have a step which I don't understand.

1) I have to prove that $\prod_{k=2}^n \frac{k^3-1}{k^3+1}$ is convergent.

My first steps were:

$\prod_{k=2}^n \frac{k^3-1}{k^3+1}= \prod_{k=2}^n \frac{k-1}{k+1}\cdot \prod_{k=2}^n \frac{k^2+k+1}{k^2-k+1}=\frac{2(n-1)!}{(n+1)!}\prod_{k=2}^n \frac{k^2+k+1}{k^2-k+1}$

And then I got stuck. The author of the exercise does that:

$\frac{2(n-1)!}{(n+1)!}\cdot\prod_{k=2}^n \frac{k^2+k+1}{k^2-k+1} = \frac{2}{n(n+1)}\cdot\prod_{k=2}^n((k+1)^2-(k+1)+1)\cdot\prod_{k=2}^n\frac{1}{k^2-k+1}=$ $\frac{2}{n(n+1)}\cdot\prod_{k=3}^{n+1}(k^2-k+1)\cdot\prod_{k=2}^n\frac{1}{k^2-k+1}=\frac{2}{n(n+1)}\cdot\frac{(n+1)^2-(n+1)+1}{3}=\frac{2}{3}\cdot\frac{n^2+n+1}{n^2+n}\rightarrow\frac{2}{3}$

I understand what he does, but I don't know how he knew it. How can I use it for other exercises, so does somebody know how to remember this trick and for which kind of exercises this works?

2) I have to prove that $a_n:=\sqrt{n^2+n}-n$ is convergent and that a constant $A$ exist with $|a_n-a|<\frac{A}{n}.$

I proved that $a_n$ is convergent to $\frac{1}{2}$. For finding the constant $A$ the author says

It's easy to see, that: $|a_n -\frac{1}{2}|=|\frac{n}{\sqrt{n^2+n}+n}-\frac{1}{2}|<\frac{1}{8n}$, therefore $A:=\frac{1}{8n}$.

Unfortunately I don't see it. Can somebody please give a hint how he gets $\frac{1}{8}$?


share|cite|improve this question
Therefore $A=\frac18$ and not $A=\frac1{8n}$. – Did Sep 25 '11 at 10:54

1) Factoring further $$ \begin{align} k^3-1&=(k-1)(k^2+k+1)=(k-1)(k+\alpha)(k+\bar{\alpha})\\ k^3+1&=(k+1)(k^2-k+1)=(k+1)(k-\alpha)(k-\bar{\alpha}) \end{align} $$ where $\alpha+\bar{\alpha}=1$. It is easy to see that $\prod\frac{k-1}{k+1}$ is telescoping. However, when we write $\prod\frac{(k+\alpha)(k+\bar{\alpha})}{(k-\alpha)(k-\bar{\alpha})}=\prod\frac{(k+1-\bar{\alpha})(k+1-\alpha)}{(k-\alpha)(k-\bar{\alpha})}$, it becomes evident that this telescopes, too.

2) $$ \begin{align} \left|\frac{n}{\sqrt{n^2+n}+n}-\frac{1}{2}\right| &=\frac{1}{2}\left|\frac{n-\sqrt{n^2+n}}{n+\sqrt{n^2+n}}\right|\\ &=\frac{1}{2}\frac{n}{(n+\sqrt{n^2+n})^2}\\ &<\frac{1}{2}\frac{n}{4n^2}\\ &=\frac{1}{8n} \end{align} $$

share|cite|improve this answer

1) The author uses a trick to compute the exact value of the infinite product but one does not need it to show the convergence only.

Namely, use that $\frac{k^3-1}{k^3+1}=1-\frac2{k^3+1}$, that $\frac2{k^3+1}<1$ for every $k\ge2$ and that the series $\sum\limits_{k}\frac2{k^3+1}$ converges absolutely.

2) Use the trick of the conjugate quantity, that is, $\sqrt{x}-\sqrt{y}=\frac{x-y}{\sqrt{x}+\sqrt{y}}$ for positive $x$ and $y$.

Thus, $a_n=\frac{n}{\sqrt{n^2+n}+n}$ (choose $x=n^2+n$ and $y=n^2$) hence $1-2a_n=\frac{\sqrt{n^2+n}-n}{\sqrt{n^2+n}+n}$, which is also $1-2a_n=\frac{n}{(\sqrt{n^2+n}+n)^2}$ (same $x$ and $y$). Since $\sqrt{n^2+n}+n\ge2n$, this shows that $0\le 1-2a_n\le\frac1{4n}$, hence $2a_n\to1$ and, as the author writes, $\frac12-\frac1{8n}\le a_n\le\frac12$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.